Gestión de riesgos del trabajo en el área de talleres y bodegas del GADMI del cantón Pujilí en el 2024. - Morales Chiluisa, Byron Javier (2025)
This research project aims to “Manage work risks in the workshops and warehouses of the GADMI in the Pujilí canton through the use of validated methods to intervene with control measures for the associated risks.” After analyzing the initial conditions, descriptive, non-experimental, and field research techniques are established for collecting information. A survey and checklist were applied to identify risks. As a result, the workers were exposed to types of risks, such as physical, mechanical, and ergonomic, due to the lack of culture in industrial safety. In the risk assessment, the INSHT, WILLIAM FINE, RULA, GINSHT, CHECKLIST OCRA methodologies and other methodologies validated in the legal framework in force in Ecuador and internationally were used, in addition to using measuring equipment for the identified physical risks; this establishes the estimate of each risk to which the workers are exposed. As a result of the research project, the presence of significant risks that could affect the safety and health of workers was evident, which is why there is a need to propose appropriate control measures to mitigate these risks through an occupational risk prevention plan.